Epidemiology of COVID-19 in Jiangxi, China: A retrospective observational study. Issue 43 (29th October 2021) - Dong, Yonghai; Ding, Sheng; Zhang, Jingyu; Liu, Yun
Abstract : Abstract: To analyze the epidemiological characteristics of coronavirus disease 2019 (COVID-19) in Jiangxi Province, China, from January 21 to April 9, 2020. COVID-19 epidemic information was obtained from the official websites of the Jiangxi Provincial Health Committee, Hubei Provincial Health Committee, and National Health Commission of the People's Republic of China. ArcGIS 10.0 was used to draw a map of the spatial distribution of the cases. On January 21, 2020, the first COVID-19 confirmed case in Jiangxi was reported. By January 27, COVID-19 had spread rapidly to all cities in Jiangxi. The outbreak peaked on February 3, with a daily incidence of 85 cases. The last indigenous case reported on February 27. From January 21 to April 9, a total of 937 confirmed cases of COVID-19 were reported, with a cumulative incidence of 2.02/100, 000. Of those, 936 patients (99.89%) were cured, and 1 (0.11%) died due to COVID-19. The COVID-19 epidemic trend in Jiangxi was basically consistent with the national epidemic trend (except Hubei). Throughout the epidemic prevention and control phase, Jiangxi province has taken targeted prevention and control measures based on the severity of the spread of COVID-19. The COVID-19 epidemic in Jiangxi was widespread and developed rapidly. In less than 1 month, the epidemic situation was effectively controlled, and the epidemic situation shifted to a low-level distribution state. All these proved that the COVID-19 prevention and control strategies and measures adopted by Jiangxi Province were right, positive and effective.